Professional attractiveness among long-term care workers in nursing homes in China: a cross-sectional study - Xiaojing Qi; Ziyan Dong; Wen Xie; Liuqing Yang; Jie Li (BMC, 2024)
Abstract Background The population aging trend and the shortage of elderly care workers require the long-term care profession to become more attractive. However, the professional attractiveness among long-term care workers has yet to be extensively studied. This study aims to identify the factors that influence the attractiveness of the long-term care profession for nursing home (NH) care workers.. Methods A cross-sectional study was conducted in more than 50 NHs. Perception of professional attractiveness among long-term care workers and potential associated factors were measured using the Attractive Work Questionnaire (AWQ) and structural instruments including the Fraboni Scale of Ageism (FSA) and the Maslach Burnout Inventory (MBI). A multiple linear regression method was employed to explore the influence of potential independent variables on professional attractiveness. Results The overall response rate was 99%. The results showed the score of professional attractiveness (185.37 ± 20.034), as well as the scores of each component (99.26 ± 11.258 for work condition, 30.13 ± 3.583 for work content, and 55.99 ± 7.074 for job satisfaction). Findings of multiple linear regression analysis indicated that age(β = 0.129, p<.05), years of work(β = 0.156, p<.05), 12-hour shifts(β = 0.185, p<.05), and training times per year(β = 0.148, p<.05) positively associated with long-term care workers perceived professional attractiveness. Whereas only ageism(β=-0.267, p<.05) significantly and negatively influenced professional attractiveness. Conclusions The perceived professional attractiveness of long-term care workers in NHs was acceptable. Age, years of work, shifts, training opportunities, and ageism contributed to the professional attractiveness of nursing home care workers in China. Target intervention measures should be taken to enhance the attractiveness of long-term care careers so as to avoid the shortage of long-term care workers.